HUBUNGAN PERUBAHAN TUTUPAN LAHAN TERHADAP FENOMENA URBAN HEAT ISLAND (UHI) DI KOTA PEKANBARU TAHUN 2001, 2009, DAN 2019 - Danny Akbar; Endah Purwaningsih (JURUSAN GEOGRAFI FIS UNP, 2021)
This study aims to identify 1). Changes in Land Cover and Changes in Surface Temperature in Pekanbaru City in 2001, 2009 and 2019 and 2). Analyzing the Relationship Between Land Cover Change and the Urban Heat Island (UHI) Phenomenon in Pekanbaru City from 2001, 2009 and 2019. The methods used in this study are 1). Supervised, 2). Land Surface Temperature, and 3). Multiple Regression test and that the results are 1). Every year there is a significant reduction in forest land cover, changing to plantation land cover and developed land, 2). There is an influence between changes in land cover on temperature in Pekanbaru City with a strong relationship of 0.637 followed by the direction of Urban Heat Island development to the south of the city of Pekanbaru